Effect of Fiber Type, Water Content, and Velocity on Wetness Perception by the Volar Forearm Test: Threshold Detection Test. (February 2020) - Zhang, Zhaohua; Tang, Xiangning; Wang, Yunyi; Li, Jun; Tian, Miao
Two kinds of evaluation methods were applied to gain insight into how fabrics affect the perception of wetness under dynamic skin contact at different velocities. In a previous study, the stimulus intensity rating was tested by applying a fixed amount of water to fabric samples to determine the quantitative ratings for the intensity of the perception of wetness. In this study, the perceived threshold was determined by supplying water continually until the level of wetness was just-detectable. The results indicated positive correlations between the fabric coefficient of friction, the water spreading speed, and the wetness perception threshold, and there were negative correlations between fabric wetting time, skin cooling rate, and wetness perception threshold. However, no correlation between wetness threshold and maximum transient thermal flow ( Q max ) was found in this study. The wetness threshold can be predicted by wetting time and coefficient of friction ( R 2  = .70, p  <   .001). The threshold detection was qualified to evaluate the sensitivity to wetness at the initial detection of moisture on the skin, while the stimulus intensity rating would give a better prediction at the moisture absorption stage. This study provided the evaluation technology for designing sportswear, leisurewear, and health-care products with desirable wetness levels.